Vegetative chronic genital herpes with satisfactory response to imiquimod - Stella Meireles Siqueira; Bruna Barroso Gonçalves; Julia Bozetti Loss; Rogerio Ribeiro Estrella (Sociedade Brasileira de Dermatologia, 2019)
Abstract Vegetative chronic genital herpes is an atypical presentation of herpes simplex 2 that it is usually seen in patients coinfected with human immunodeficiency virus. Clinically, it is characterized by extensive ulcers that evolve to chronification and hypertrophic pseudotumor forms. Antiviral drugs are recommended for the treatment, and acyclovir is the most used one. Foscarnet is the treatment of choice to resistant cases, although treatment failure has been reported. We report a male patient, previously diagnosed with human immunodeficiency virus who developed vegetative chronic genital herpes resistant to acyclovir and successfully treated with imiquimod.